2018
DOI: 10.2147/idr.s153116
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility testing of vulvovaginal <em>Candida</em> species among women attending antenatal clinic in tertiary care hospitals of Peshawar

Abstract: BackgroundVulvovaginal candidiasis (VVC) is considered as a pervasive gynecological problem among women worldwide. Owing to this fact, in the current study, we aimed at assessing the prevalence rate of Candida spp. causing VVC in symptomatic pregnant women and their antifungal susceptibility pattern.MethodsThis study was carried out in the tertiary care hospitals of Peshawar during the period of July 1, 2016 to December 31, 2016. The study group included 450 pregnant women in the age group of 17–44 years with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
46
7
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 29 publications
12
46
7
9
Order By: Relevance
“…China, Brazil, Tunis, Kuwait, India, Greece and Turkey have reported that C.albicans remains the most commonly isolated yeast (60%-80%) in women diagnosed with VVC [21][22][23][24][25][26][27]. On the other hand, an increasing trend in the occurrence of NCAC (58%-60%) over time has also been observed in Pakistan and Burkina Faso [28,29]. The main identified NCAC in our study were C.glabrata (71%, N = 41) followed by C. krusei (29%, N = 17).…”
Section: Resultsmentioning
confidence: 98%
“…China, Brazil, Tunis, Kuwait, India, Greece and Turkey have reported that C.albicans remains the most commonly isolated yeast (60%-80%) in women diagnosed with VVC [21][22][23][24][25][26][27]. On the other hand, an increasing trend in the occurrence of NCAC (58%-60%) over time has also been observed in Pakistan and Burkina Faso [28,29]. The main identified NCAC in our study were C.glabrata (71%, N = 41) followed by C. krusei (29%, N = 17).…”
Section: Resultsmentioning
confidence: 98%
“…According to various data (Bradford & Ravel, 2017;Bitew & Abebaw, 2018), the detection rate of C. albicans is at least 35-45%, which is confirmed by the results obtained by us. Accordingly, the total frequency of detection of nonalbicans Candida species is more than 50% (Liu et al, 2014;Khan et al, 2018). Separately, species such as C. glabrata and C. krusei are quite common.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to perform correction of the conditions that lead to the development of genital candidiasis. Use of multivitamin complexes may be beneficial (Mendling et al, 2015;Pappas et al, 2016;Khan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women in the third trimester were mostly affected by VVC unlike a similar study in Peshawar which reported most infections in the second trimester. [26] C infections. [31] In such cases, it's recommended that liposomal amphotericin B is used in addition to managing the source of the infection.…”
Section: Prevalence and Phenotypic Characterization Ofmentioning
confidence: 99%